ICTs' Spatial Diffusion Waves - Anastasia Nagirnaya (European Regional Science Association (ERSA), 2014)
Spatial diffusion of information and communication technologies (ICTs) is a global continuous accumulative process. But is it uniform or cyclic? Is it possible to skip some of its historical stages? What is a specific feature of the modern stage? Are there any patterns of ICTs interaction? And how do different ICT innovations work on globalization? Based on official statistics on ICTs penetration and traffic (print press, postal service, telegraph, telephone, radio, television, mobile phone, Internet) received from governments (including USA and Russia) and international organizations (ITU, UN, etc.) covering the period of the latest 20–150 years, graphs and maps have been generated and the following results have been obtained. The study has shown that ICTs diffusion is wave-like in the long term. As a rule, new innovation waves accelerate a decline of the old ones. But in some cases, when waves of different ICT generations overlap, a "resonance effect" appears caused by the inertness of ICT infrastructure. Detailed analysis of mobile telephony diffusion in correlation with fixed telephony and Internet revealed a fact that advanced ICTs development can make it possible for developing regions to skip certain stages of informatization and even implement an "overcoming" scenario of catching-up development. Specific feature of the modern stage is ICTs convergence: an integrated universal system of global digital communications is being developed on the Internet basis. It is an outcome of the modern globalization age, just as telegraph formed the 1st global information network in early globalization epoch. According to our research of different ICTs' traffic structure, each next generation of ICT innovations provides more international communicative openness (defined by a share of international traffic in a total traffic volume). In the modern world only 4% of the global telephone traffic is international, just 1% of the traditional postal mail crosses international borders. Another trend has been discovered for the Internet traffic, 46% of which is international, and this share is growing rapidly. Thus, when moving from traditional to the newest ICTs, a spatial scale of communication grows from mostly local to international, and international traffic is constantly migrating from traditional to the newest telecommunications. This study expands the understanding of ICTs diffusion process, presenting it in a long term and in an integrated manner, and its results could be important for informatization policies and strategies elaboration.
Keywords: 330; innovations diffusion; information and communication technologies; telecommunications